Humic acid characterization in soil from various land uses in Tutur District, Pasuruan Regency of East Java - M Ghufron Chakim; Wanti Mindari; S Siswanto; Purnomo Edi Sasongko (Brawijaya University, 2020)
Changes in land use will impact on the characteristics of humic acid in the soil due to biotic and abiotic factors. The study aimed to characterize humic acid in soil from various land uses in Tutur District, Pasuruan Regency of East Java. Soil sampling was carried out on six land uses, namely mixed garden, coffee plantation, apple orchard, vegetable garden, pine forest, and conservation forest. Analysis of soil samples included soil chemical characteristics (pH, redox, organic-C, and total-N) and characterization of humic acid included colour ratio of E4/E6, total acidity, carboxyl groups, and phenolic groups. The results showed that the land use of coffee plantation provided the best soil fertility indicated by the contents of humic acid, total-N, organic-C in the soil that were higher than that of other land-uses. The highest humification index was obtained for coffee plantation land use with the measurement of the E4/E6 colour ratio of 4.56 index value. The best characteristics based on the total value of acidity, the -COOH group and the phenolic -OH group were observed in the coffee plantation. This was supported by the characteristic of humic acid through the humification index or E4/E6 colour ratio, as well as the low phenolic -OH value which is a characteristic of fulvic acid.